Typosquatting Crime in the Electronic Transactions (Law Research Review Quarterly, 2021)
Today's technological developments have brought many changes to human life. This change will certainly bring benefits to life, including making all transactions easier and faster. However, there are still some parties who take advantage of technology to act crimes. Among them is typosquatting, which is impersonating a domain name that is almost similar to the original domain name and has the same contents as the original domain. This will be detrimental to transaction service users. This research aims to analyze and study typosquatting in electronic transactions in Indonesia and its law enforcement. This study found that these crimes often committed on the internet were used to trick internet users by creating a fake website using names that were very similar to well-known websites. Furthermore, this research underlines that typosquatting legal arrangements in Indonesia can be seen in the Trademark Law, the Criminal Code, as well as the Information and Electronic Transaction Law.